Heart Dosimetric Parameters Were Associated With Cardiac Events and Overall Survival for Patients With Locally Advanced Esophageal Cancer Receiving Definitive Radiotherapy - Cai, Guoxin; Li, Chuanbao; Yu, Jinming; Meng, Xue (Frontiers in Oncology, 2020)
Objectives: To assess the association between heart dosimetric parameters and cardiac events or overall survival (OS) for patients with stage III esophageal cancer receiving definitive radiotherapy. Materials and methods: Patients with stage III esophageal cancer receiving definitive radiotherapy at our hospital from 2011 to 2013 were enrolled retrospectively. The primary endpoint was grade ≥ 2 cardiac events and the second endpoint was five-year OS. Competing risks analysis and Cox regressions analysis were performed to evaluate the association between heart dose and cardiac events or OS. Results: Three hundred and forty-six patients were analyzed. Median follow-up was 30 months. Median prescribed dose was 60 Gy. Seventy-eight patients (22.5%) had ninety-one grade ≥ 2 cardiac events, at a median of 14 months to first event. Thirty-three patients (9.5%) had forty-two grade ≥ 3 cardiac events. Of the 78 patients with grade ≥ 2 cardiac events, 70 (89.7%) had the first cardiac events that occurred within first three years after radiotherapy. Multivariable analysis showed that pre-existing ischemic heart disease (hazard ratio (HR), 2.26; 95% confidence interval (CI), 1.26-4.06; p = .006) and mean heart dose (HR, 1.12; 95% CI, 1.04-1.20; p = .002) were significantly associated with increased risk of grade ≥ 2 cardiac events. Disease progression (HR, 2.60; 95% CI, 1.82-3.70; p < .001), Eastern Cooperative Oncology Group (ECOG) performance status (HR, 0.71; 95% CI, 0.56-0.91; p = .007), heart lung volume receiving ≥ 5 Gy (V5, HR, 1.01; 95% CI, 1.00-1.03; p = .035), and gross tumor volume (GTV, HR, 1.00; 95% CI, 1.00-1.00; p = .020) were significant predictors of five-year OS on multivariable analysis. Conclusion: Higher heart dose was significantly associated with an increased cardiac event rate and a worse OS outcome for patients with stage III esophageal cancer treated with definitive radiotherapy. Most of the first cardiac events occurred within first three years after treatment.